Implementasi Metode HSI pada Transformasi Ruang Warna Dalam Mendeteksi Kematangan Buah Mangga Udang - Yuni Franciska Br Tarigan; Karina Andriani; Rika Rosnelly; Wanayumini Wanayumini (Universitas Budi Darma, 2022)
Mango is a plant that is widely cultivated in Indonesia. Mango is a fruit that is popular and favored by almost the entire world population. Mango is not a native plant from Indonesia but is a fruit plant native to India that has a distinctive taste. The shelf life is very short because it is a fruit that is easily damaged or rotted in a certain period of time. The use of technology Digital image is an image that can be processed directly by a computer. A digital image can be represented by a matrix consisting of M columns and N rows, where the intersection between the columns and rows is called a pixel (picture element), which is the smallest element of an image. Image processing is a form of processing an image or image by numerical processing of the image, in this case, each pixel or point of the image is processed. One image processing technique utilizes a computer as software to process each pixel of an image. For image processing applications that perform object recognition, it will be easier if the object is identified using the difference in its hue value by limiting a certain value of the hue value to the object. The HSI color space model is a color space system similar to the performance of the human eye. HSI works by combining the color or grayscale contained in the image. Based on the reference value range of the Mango Shrimp fruit that has been determined in the process using the HSI method, it can be concluded that the test image of the Mango Shrimp fruit with a value of H=32 S=0.675 I=83 then the manga can be said to be ripe.